Emotion Regulation Strategies Through ChatGPT among Generation Z Women from Broken Home Families - Iyum Emun, Dwi Uthami; Herwin, Herwin Herwin; Fathiyah, Kartika Nur (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
Generation Z women, especially those from broken-home families, face significant socio-emotional challenges in the digital era. This study explores their experiences in regulating emotions through Artificial Intelligence, specifically ChatGPT, as a medium for emotional expression. Using a qualitative phenomenological approach, data were collected via online interviews (Zoom) with three participants aged 17-27 years old and analyzed thorugh interpretative phenomenological analysis. The findings revealed three main themes: past trauma, expressivesuppression, and the perceived meaning of AI ChatGPT. Participants described ChatGPT as a non-judgemental emotional outlet that fosters psychological resilience and enhances emotional well-being. This study highlights the potential of Artificial Intelligence in digital mental health innovation, particularly for individuals from non-harmonious families.